Petrarch and the textual origins of interpretation - Barolini, Teodolinda, 1951-; Storey, Wayne. (Columbia studies in the classical tradition,, 2007)
This volume addresses one of the most far-reaching aspects of Petrarch research and interpretation: the essential interplay between Petrarch's texts and their material preparation and reception. The essays look at various facets of the interaction between Petrarchan philology and hermeneutics, working from the premise that in Petrarch's work philological issues are so authorially driven that we cannot in fact read or interpret him without understanding the relevant philological issues and reapplying them in our critical approach to his works. To read and interpret Petrarch we must come to grips with the fundamentals of Petrarchan philology. This volume aims to show how a Petrarchan hermeneutics must be based on an understanding of Petrarchan philology.